Hydrogen sulfide as a new therapeutic target of pulmonary hypertension: an overview with update on immunomodulation - Zhu, Xue-Xue; Zhao, Chen-Yang; Lu, Qing-Bo; Zhang, Ao-Yuan; Meng, Xin-Yu; Su, Jia-Bao; Chen, Guo; Xu, An-Jing; Sun, Hai-Jian; Nie, Xiao-Wei (Frontiers in Pharmacology, 2025)
Pulmonary hypertension (PH) is a complex and progressive vascular disease characterized by elevated pulmonary arterial pressure (PAP) and vascular resistance, leading to right ventricular failure and, ultimately, death. Current therapies primarily focus on vasodilation and symptom management, but there remains a critical need for treatments that address the underlying pathophysiological mechanisms of PH. Numerous studies have identified hydrogen sulfide (H2S) as a potential therapeutic target in PH. Traditionally recognized for its toxic effects at high concentrations, H2S is now known to play crucial roles in various physiological processes, including vasodilation, anti-inflammation, and antioxidation, which are relevant to PH pathogenesis. Given its multifaceted roles in the pathophysiology of PH, H2S represents a promising therapeutic target. Strategies to enhance endogenous H2S production or administer exogenous H2S donors are being explored as potential treatments for PH. These approaches aim to harness the vasodilatory, anti-inflammatory, antioxidant, and anti-remodeling properties of H2S to mitigate disease progression and improve patient outcomes. Future research should focus on optimizing H2S-based therapies and exploring their clinical efficacy and safety in PH patients.